(untitled) (Gilgameš, 2016)
The rebirth of popular imagerie is known to be one of the most relevant artistic facts of the Great War’s France, where the logics of wide circulation of the image, linked to propaganda needs, meet with the avant-gardes figurative researches. This paper aims to focus the spread of this form of artistic production and the associated development of a highly specialized editorial system. Illustrators and artists take part with different orientations to the industry of patriotic prints working both for the maison d’édition network and for magazines. Some of the most conscious authors, such as Raoul Dufy and André Lhote, implement innovative visual and poetics strategies, programmatically opting for photomechanical reproduction techniques to create their images. The multiplication of this explicit war iconography succeed also in the applied arts field, where it maintains its vitality throughout the early post-war period and significantly characterize the taste of part of the art production presented at the great Exposition Internationale des Arts Décoratifs et Industriels Modernes held in Paris in 1925.